2001
DOI: 10.1034/j.1600-0706.2001.950217.x
|View full text |Cite
|
Sign up to set email alerts
|

What a wonderful web they weave: spiders, nutrient capture and early ecosystem development in the high Arctic – some counter‐intuitive ideas on community assembly

Abstract: Spiders are the earliest colonisers of newly exposed moraine substrates on the glacier foreland of the Midtre Lovénbreen at Ny‐Ålesund, W. Spitsbergen, Svalbard (78°N). Spider densities are highly correlated with allochthonous inputs of potential prey items, predominantly chironomid midges. Large allochthonous inputs of insects potentially provide significant quantities of nitrogen and phosphorus to the developing ecosystem from the earliest stages of succession, even before a conspicuous cyanobacterial crust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 28 publications
4
89
0
Order By: Relevance
“…Although several studies have considered how soil fauna respond to ecosystem progression (e.g., Hodkinson et al 2001, Kaufmann 2001, few have considered soil faunal responses to retrogression. Williamson et al (2005) found densities of microbe-feeding and predatory nematodes to decline during retrogression in the Waitutu chronosequence of New Zealand.…”
Section: Responses Of Belowground and Aboveground Consumersmentioning
confidence: 99%
“…Although several studies have considered how soil fauna respond to ecosystem progression (e.g., Hodkinson et al 2001, Kaufmann 2001, few have considered soil faunal responses to retrogression. Williamson et al (2005) found densities of microbe-feeding and predatory nematodes to decline during retrogression in the Waitutu chronosequence of New Zealand.…”
Section: Responses Of Belowground and Aboveground Consumersmentioning
confidence: 99%
“…Other studies have focused more on the interactions between plants, organic matter production, and decomposer densities (brown web interactions; Berendse et al 1994, Moore et al 2004, Wardle et al 2004, Berg and Bengtsson 2007. However, in some of the most intensively studied successions, plants were found to play a minor role in the first stages of succession (Edwards and Sugg 1993, Kaufmann 2001, Hodkinson et al 2004 or were not even present at all (Payne 1965, Polis and Hurd 1995, Hodkinson et al 2001. This raises general questions about the extent to which the green and the brown food webs determine the onset and outcome of succession and how the importance of these food web components changes over the course of primary succession.…”
Section: Introductionmentioning
confidence: 99%
“…The use of the chronosequence as a space-for-time substitution (Foster and Tilman 2000) along glacier foreland has provided significant insights into the patterns and mechanisms of plant (Walker arthropod diversity increase throughout the succession (Hodkinson et al 2001, Gobbi et al 2010.…”
Section: Introductionmentioning
confidence: 99%